An Extensive Study on the Performance Evaluation and Scheduling of HeNBs - Paulo, Rui R. (2021)
Since the dawn of mobile communication systems, reducing the cell size has been one option to increase the signal-to-interference-plus-noise ratio (SINR) in both links. The impact of this reduction can be perfectly understood by considering Shannon’s law. This work studies in detail the performance of Home eNBs (HeNBs), nodes with a smaller coverage area. After a detailed theoretical study of the SINR, a simulation approach is used to extract performance results in small cell indoor scenarios. Results corresponding to the goodput, delay and packet loss ratio are analyzed. Based on an improved version of LTE-Sim, the proportional fair, frame level scheduler (FLS) and exponential rule are tested in an indoor environment. With the saturation conditions taken into consideration, the FLS performs better than the other schedulers. This work shows that with the considered applications, it is possible to achieve a reduction in the transmitter power of HeNBs without compromising the small cell network performance.